Therapy for hepatitis C genotype 3: moving forward. Issue 9 (13th May 2015) - Buti, M.; Llaneras, J.; Riveiro‐Barciela, M.; Esteban, R.
Summary Until recently, the standard of care for hepatitis C virus genotype 3 infection was response‐guided therapy with pegylated interferon plus ribavirin for 16 to 48 or 72 weeks. The introduction of sofosbuvir plus ribavirin has revolutionized hepatitis C virus therapy. Nowadays, the recommend treatment regimen is a combination of sofosbuvir and a weight‐based ribavirin dose for 24 weeks. For easy to treat patients (e.g. naïve or previously treated patients without cirrhosis), this combination achieves high sustained virologic response rates and is well tolerated. However, in treatment‐experienced patients with cirrhosis, sustained virologic response is lower due to unknown reasons. The combination of two direct‐acting antiviral agents, sofosbuvir and daclatasvir, for 12 weeks is also associated with low sustained virologic response rates in this special population, for whom new drugs and different strategies are now under evaluation. Currently, the high cost of all these drugs limits access to treatment in many countries.